PENGARUH KEADILAN DISTRIBUTIF ROTASI KERJA DAN KEADILAN PROSEDURAL ROTASI KERJA TERHADAP KEPUASAN KERJA YANG BERDAMPAK PADA KINERJA KARYAWAN - Diana Puspitasari (MM UMY, 2015)
This study discusses the organizational justice include distributive justice of job rotation and procedural justice job rotation to employees performance both directly and indirectly influenced by job satisfaction. The populations in this study were all employees in PT. Panpages Yogyakarta. Data were collected by survey method is to provide a list of questions or questionnaires directly to the respondent. Data analysis techniques in this study using analysis of SEM (Structural Equation Modeling) program operated through AMOS 22.0 and SPSS 17.0. The results showed that distributive justice job rotation significant positive effect on job satisfaction; procedural justice job rotation significant positive effect on job satisfaction; distributive justice job rotation positive effect to employees performance; procedural justice job rotation are not significantly to employees performance; job satisfaction significant positive effect on employees performance; job satisfactions as a mediating influence of distributive justice job rotation and procedural justice job rotation to employees performance.